A model for capturing and representing the engineering design process - Gonnet, Silvio Miguel (2007)
This paper presents a Collaborative Model for capturing and representing the engineering Design process (CoMoDe). CoMoDe is a deductive object-oriented model that, in relation to an engineering design process, is able to capture the different elements that participate in a design process in an integrated fashion. In particular, it is able to represent (i) the activities, operations, and actors that have generated each design product, (ii) the imposed requirements, and (iii) the rationale behind each decision. Furthermore, it also offers an explicit mechanism to represent and trace the different model versions that have participated in the design process. On such a basis, this proposal introduces specific procedures to handle various situations appearing in cooperative environments. They are: (i) different design teams perform independent concurrent activities on ‘‘a priori’’ independent parts of the artefact being designed and afterwards their results need to be made consistent; (ii) distinct teams concurrently work on slightly coupled parts of the artefact being designed and conflict handling must be addressed along their ‘‘parallel’’ course of actions.